FEEDING ANGOR GOATS ON PASTURE (Intent Research Scientific Journal, 2023)
In the mountainous regions of our country, there are thoughts about raising goats of the Angora breed suitable for the rapidly changing climate, preserving their valuable biological characteristics, increasing the number of goats, enriching the biodiversity of plants using pasture plants, and the importance of pastures.